PERLINDUNGAN HUKUM PREVENTIF KEPADA KONSULTAN HUKUM PASAR MODAL DI INDONESIA (Studi Perbandingan Hukum Indonesia dan Singapura) - Halawa, Filemon; Situmeang, Ampuan; Amboro, FL Yudhi Priyo (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Indonesia as a sovereign country guarantees and provides protection for every citizen. This is a reflection of the State of Indonesia as a state of law. It is the same as the supporting profession of legal consultants in the capital market who have the right to have all their rights protected while carrying out their profession. The supporting profession of legal consultants in the capital market has an important role. Provisions of Article 67 of Law no. 8 of 1995 concerning the Capital Market which reads "In carrying out business activities in the Capital Market sector, Capital Market Supporting Professionals are required to provide an independent opinion or assessment. However, according to the author's careful review, in the capital market legal consultant profession, legal immunity has not been found while carrying out their profession. While in the Advocate Law there is immunity for an Advocate who carries out his functions as contained in Article 16 of Law Number 18 of 2003 concerning Advocates. The Capital Market Law does not explicitly describe legal protection for capital market legal consultants. For this reason, in this paper the author finds about preventive legal protection for capital market legal consultants in Indonesia with a Comparative Study of Indonesian and Singapore Laws. Legal Consultants in the Capital Market in Indonesia, one of the fundamental things to avoid legal sanctions is obedience to existing legal norms. While in Singapore it was found that since the beginning according to the country's constitution there has been legal immunity for professions related to Advocates, Lawyers or legal consultants. To answer the problem of this paper, the writer uses normative juridical method with progressive legal theory (Prof. Satjipto Rahardjo) and Legal Protection Theory (Philipus M. Hadjon).